Prospective Study on Soluble Thrombomodulin and von Willebrand Factor and the Risk of Ischemic and Hemorrhagic Stroke - Johansson, Lars; Jansson, Jan-Håkan; Boman, Kurt; Nilsson, Torbjörn K.; Stegmayr, Birgitta; Hallmans, Göran (Thrombosis and Haemostasis, 2002)
The aim of the present study was to examine if soluble thrombomodulin (sTM) and von Willebrand factor (VWF) could predict a first-ever ischemic or hemorrhagic stroke.This study was an incident case-referent study from within a population-based cohort in northern Sweden. Up to 1996 about 44,000 subjects had been screened and stroke cases were classified according to the WHO MONICA criteria. A first-ever stroke occurred in 108 cases. A total of 216 controls were selected from the same cohort.This prospective study found no association with sTM or VWF and the development of a first-ever ischemic stroke (n = 87) in the logistic regression model. For the hemorrhagic stroke cases (n = 18), the multivariate logistic regression model revealed a significant negative association with sTM. When dichotomized, the upper level (>17.3 µg/L) of sTM, as compared with the lower level (<17.3 µg/L), showed one fifth of the risk for hemorrhagic stroke (OR, 0.18; CI, 0.05 to 0.69). No significant association was found for VWF. We suggest that the novel finding of an inverse relation between sTM and hemorrhagic stroke should be investigated in a larger study.
Keywords: Thrombomodulin; von Willebrand factor; cerebral infarction; cerebral hemorrhage; risk factors